If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(2X + -10) + -5(7 + -1X) = 4X + -3 Reorder the terms: 4(-10 + 2X) + -5(7 + -1X) = 4X + -3 (-10 * 4 + 2X * 4) + -5(7 + -1X) = 4X + -3 (-40 + 8X) + -5(7 + -1X) = 4X + -3 -40 + 8X + (7 * -5 + -1X * -5) = 4X + -3 -40 + 8X + (-35 + 5X) = 4X + -3 Reorder the terms: -40 + -35 + 8X + 5X = 4X + -3 Combine like terms: -40 + -35 = -75 -75 + 8X + 5X = 4X + -3 Combine like terms: 8X + 5X = 13X -75 + 13X = 4X + -3 Reorder the terms: -75 + 13X = -3 + 4X Solving -75 + 13X = -3 + 4X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-4X' to each side of the equation. -75 + 13X + -4X = -3 + 4X + -4X Combine like terms: 13X + -4X = 9X -75 + 9X = -3 + 4X + -4X Combine like terms: 4X + -4X = 0 -75 + 9X = -3 + 0 -75 + 9X = -3 Add '75' to each side of the equation. -75 + 75 + 9X = -3 + 75 Combine like terms: -75 + 75 = 0 0 + 9X = -3 + 75 9X = -3 + 75 Combine like terms: -3 + 75 = 72 9X = 72 Divide each side by '9'. X = 8 Simplifying X = 8
| (21a-15b+33c)= | | 3(4x-3)=13x | | 7*(3m+9n-18p)= | | 3x-10(x+2)=13-7x | | 5+2x-16=10-7x+21 | | 12=6-(x-3) | | -4h+2=18 | | x+5=-4x | | 7(x-6)=4x+(3x+10) | | 6(x+3)-27=15 | | x+20+10x=20+9x | | 58x=580 | | 400=-20w | | -4+7x=10 | | 6x+2y=12 | | 11u=-88 | | 51-14v=569 | | -72=8x | | (x-5)(x+7)= | | 4-3w=-2 | | 6p=18 | | -3u=-48 | | 54=2v | | 3x=-33 | | 12t=84 | | 9-0.8(y-3)=1 | | -4n=100 | | 0.4x+11=7 | | 8+x-5=10 | | 7(-2)-3(3)= | | 5(-2)(3)-2= | | 5-2(3)-2= |